The Effect of Flipped Classroom Model on the Ability to Write News Text in Class VII SMP Negeri 3 Telagasari - Amanda Nasyilah; Hendra Setiawan; Slamet Triyadi (Global READ Center, 2026)
This research is motivated by the low ability to write news texts among seventh grade students of SMPN 3 Telagasari, which is indicated by difficulties in finding and developing ideas, lack of understanding of structure, and low interest in learning. Therefore, this study aims to determine the effect of using the flipped classroom model on the ability to write news texts in seventh grade students of SMP Negeri 3 Telagasari. The method used is quasi-experimental with a non-equivalent control group design. The research sample consisted of class VII B and class VII A at SMP Negeri 3 Telagasari. Data collection techniques used were observation, writing tests, documentation, and questionnaires. Data analysis techniques used statistical tests. The results of the study showed an increase in pretest and posttest results. The results of the t-test with the Independent Sample T Test were 0.000 <0.05, so H0 was rejected and Ha was accepted. The results of the student perception questionnaire with TCR analysis showed an average of 87.6% of target respondents, in the very good category. Thus, the use of the flipped classroom model has an effect on improving the ability to write news texts in class VII students of SMPN 3 Telagasari.